PERILAKU POLITIK TIDAK MEMILIH MASYARAKAT KECAMATAN TAMPAN DALAM PILKADA KOTA PEKANBARU TAHUN 2011 - Arianto Azis; Ishak, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study carried out to analyze the political behaviour being not vote of tampan district community in Pekanbaru city election on 2011. Tampan district community in pekanbaru city election on 2011only had a participation rate of 45,2%, so the author is interested in analyzing the political behaviour of the society. As for the problem in this study is why many voters who are not using their right in pekanbaru city election on 2011 in tampan district and what factors that influence.This study is qualitative study, the data collection techniques is descriptive analysis. This research uses documentation (observation) and interviews with key informants as an information object that aims to achieve the goal to get the information in this study. The type of data used in this study are primary and secondary data obtained from direct observation and interviews with key informants in this study.Based on the analiysis of the political behaviour being not vote of Tampan district community in Pekanbaru city election on 2011. It can be concluded that the public has a low rate of only 45,2% participations. It is caused by the political behaviour of the people who are not looking to sympathetic to political process that occurs (Pekanbaru City election 2011) as for some of the thing that cause political behaviour that tends to be negative are the factor of busyness community and publict distrust of promises of political appointment are common in the elections, as well as lack of political education about the essence of the elections to the Tampan district community.Key note : Political behaviour being not vote.